Leveling the Unleveled? Syariah Advocates’ Struggle for Equality in Indonesian Legal Pluralism - Ratno Lukito (Al-Jami'ah: Journal of Islamic Studies, 2011)
One of the ongoing problems faced by many Syariah advocates in Indonesia is how they can maintain their important role in the practice of law in the midst of the domination of common advocates. They are always trapped in double burden in concern of their position. On one side, they are challenged with the long historical inequality of educational access between religious (Islamic) groups and secular groups, while on the other, they have to deal with the problem of being part of Muslim society with a legal culture where Islamic  law is commonly viewed as irreconcilable with secular legal traditions. This paper specifically discusses the role played by the Association of Indonesian Syariah Advocates (Asosiasi Pengacara Syariah Indonesia, APSI) in their struggle to assert equality between Syariah advocates and common advocates. It shows that although APSI has successfully attracted attention from the state and public in general, the interest shown by Syariah faculties remains even relatively low. Embedded traditional culture of studying Islamic law in many Syariah faculties seems to have influenced their attention towards APSI. Yet, with inclusive approaches in expanding the institution, APSI can attract many advocates, not only from Muslim law graduates but from those of non-Muslims as well.